Effect of active smoking on the tympanometry findings in adult men. - Hussain, Taghreed A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Tympanometry findings are considered by many investigators to be associated with passive and active smoking. Patients and methods: One hundred forty healthy adult men aged (20-50 years). 70 smokers and 70 nonsmokers were recruited for the study. The examination included otoscopy, and screening tympanometry. Smoking history was ascertained by self –report. For each subject, age, smoking status and number of cigarettes per day were noted. Results: There is a tendency for more negative middle ear pressure in smokers than in non-smokers though this difference may not clinically significant. There were no significant differences in ear canal volume, middle ear compliance and presence of Stapedial Reflex in both smokers and non-smokers groups. There was no correlation between middle ear pressure and duration of smoking and number of cigarettes smoked amongst smokers. Conclusion; A definitive study with a larger sample size is needed to explore the effects of smoking on findings of tympanometry in healthy men.